Vancomycin resistant Enterococcus spp (VRE) : follow up during 9 years in a tertiary teaching hospital in southern Brazil - Sandri, Ana Maria (2014)
Introduction: Infection with vancomycin-resistant Enterococcus spp (VRE) has been a worldwide problem since mid 1980’s and, in Brazil, since 1996. This study was conducted to evaluate the experience with VRE in our institution. Methods: A prospective cohort study from 2000 to 2009 was conducted at Hospital São Lucas da PUCRS. All hospitalized patients with VRE positive culture were included and followed from their diagnosis until they were negative for VRE or their discharge. Only the first admission for each VRE positive patient was included. Pulsed field gel electrophoresis (PFGE) was performed to determine how VRE had spread. Results: A total of 315 cases of VRE were identified, 224 of which were isolated from rectal swabs. Vancomycin-resistant/ampicilin susceptible Enterococcus faecalis were identified in 312 isolates. PFGE was performed in 47 VRE isolates that presented an indistinguishable migratory profile. The median length of hospital stay and length of stay before VRE isolation were 46 days and 21 days, respectively; 52% of the patients were aged 60 and above. The annual distribution of the new VRE cases showed a clear decrease from 2000 to 2009. Discussion: This study shows a substantial VRE colonization (71%) with a homogenous pattern that emphasizes its transversal spread. Predominance of E. faecalis differs from the literature which largely describes a higher prevalence of vancomycin-resistant Enterococcus faecium. The follow up of VRE during 9 years in our institution highlighted the importance of continuous surveillance to prevent outbreaks in our hospital.